Democracy, Pedagogical Renewal and Rural Territory: The Valencian Comarca Agricultural School «La Serranía» - Agulló Díaz, Mª Carmen; Paya Rico, Andres (Historia y Memoria de la Educación, 2018)
The emergence in France of the Maisons familiales d’apprentissage rural in the 1930s bought the inclusion of active pedagogy and codetermination to agricultural professional education. This approach impelled the experiments in cooperativism of the Valencian Escuelas Agrícolas Comarcales that were created in Spain during the last years of Franco’s dictatorship, and that were further developed during the political transition to democracy, in order to meet the demand for improved education and cultural capitalization of the countryside. Among these experiences, it is worth noting that of the rural population of Chulilla (Valencia —the subject of the following study— as it shows the implementation of educational practices based on democratic management and pedagogical renewal. The analysis and study of this brief but meaningful experience in the history of Valencian education reveals the way in which an educational community is able to build a critical school where freedom is practiced while at the same time holding on to its origins. By resorting to oral sources, we have been able to recover the memory of their protagonists, a part of the history of this cooperative initiative of rural education, analyzing both pedagogical assumptions on which it was based (active methodology, alternation, codetermination, democracy, personal development, etc.), as well as its development in daily practice